Study on Primary Influencing Factors of Flavor Components Produced by Bacillus sp. Isolated from Black Part of Maotai Daqu. Issue 1 (June 2020) - Li, Hui; Qu, Yang; Tian, Wenjie; Wang, Xiaoqing; Shi, Ben; Tang, Yuan; Zhou, Hongyu; Bai, Yuhe; Cao, Lina; Dong, Qi; Liu, Xinrui; Tian, Shuting; et al.
Abstract: Microbes are major contributors to the unique fragrance of Maotai liquor, in which Bacillus sp. is recognized as the main flavor-producing strain. However, studies with respect to the importance, sensitivity and optimal ranges of the factors influencing the flavor components secreted by Bacillus sp. have not been reported. In this paper, a thermophilic flavor-producing strain Bacillus sp., isolated from the black part of Maotai Daqu, was chosen as the representative to study how the factors (inoculum size, temperature and incubation time) influenced the production of flavor components (acetic acid, 2, 3-butanediol and ethyl oleate). The optimal combination of factors as well as the quadratic mathematical model of flavor-producing process were obtained through central composite design analysis by batch tests. Results showed that the simulation accuracy of nonlinear equations for the production of three different types of flavor components was 96.00, 87.76, and 90.54%, respectively. Temperature was the most significant factor influencing the production of flavor components, followed by incubation time, and inoculum size showed the smallest impact. In conclusion, the optimized zones of the three factors were as follows: temperature of 38°C∼45°C, incubation time of 13∼15 d, inoculum size of 14∼17%.